2018
DOI: 10.3389/fpsyg.2017.02243
|View full text |Cite
|
Sign up to set email alerts
|

Gambling-Related Distortions and Problem Gambling in Adolescents: A Model to Explain Mechanisms and Develop Interventions

Abstract: Although a number of gambling preventive initiatives have been realized with adolescents, many of them have been developed in absence of a clear and explicitly described theoretical model. The present work was aimed to analyze the adequacy of a model to explain gambling behavior referring to gambling-related cognitive distortions (Study 1), and to verify the effectiveness of a preventive intervention developed on the basis of this model (Study 2). Following dual-process theories on cognitive functioning, in St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 67 publications
(99 reference statements)
10
39
0
Order By: Relevance
“…Here, gamblers enter a self-deception loop in which the odds of winning appear greater than the possible losses. These results are in line with previous findings among both adult (Ciccarelli et al 2016a, b;Labrador et al 2020) and adolescent samples (Ciccarelli et al 2017;Cosenza and Nigro 2015;Cosenza et al 2019;Donati et al 2018) and confirm the role of cognitive distortions in fostering gambling involvement.…”
Section: Discussionsupporting
confidence: 92%
“…Here, gamblers enter a self-deception loop in which the odds of winning appear greater than the possible losses. These results are in line with previous findings among both adult (Ciccarelli et al 2016a, b;Labrador et al 2020) and adolescent samples (Ciccarelli et al 2017;Cosenza and Nigro 2015;Cosenza et al 2019;Donati et al 2018) and confirm the role of cognitive distortions in fostering gambling involvement.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, misconceptions about gambling appear to constitute a convincing predictor of gambling problems (Barrault & Varescon, 2012;Devynck, Giroux, & Jacques, 2012;Fortune & Goodie, 2012;Joukhador, Blaszczynski, & Maccallum, 2004;Lévesque, Sévigny, Giroux, & Jacques, 2018;Mathieu, Barrault, Brunault, & Varescon, 2018;Miller & Currie, 2008;Oei, Lin, & Raylu, 2008;Toneatto, 1999;Toneatto, Blitz-Miller, Calderwood, Dragonetti, & Tsanos, 1997;Toplak, Liu, Macpherson, Toneatto, & Stanovich, 2007) as well as among adolescents (Cosenza & Nigro, 2015;Donati et al, 2018). This research suggests that gambling-related misconceptions serve an important developmental role in the learning process gamblers undergoes during some of their first early gambling experiences, and may provide a fruitful avenue for early intervention or prevention of gambling problems.…”
Section: Recommendation 1: Shift the Focus Away From Harms To Increasmentioning
confidence: 81%
“…A number of empirical studies have concluded that misunderstanding gambling-related mathematics concepts plays an important role in the development and maintenance of gambling problems, and that better understanding these might help prevent the onset of problems (Donati et al, 2018;Ferland, Ladouceur, & Vitaro, 2002;Ladouceur, Ferland, & Vitaro, 2004;Ladouceur, Ferland, Vitaro, & Pelletier, 2005;Lavoie & Ladouceur, 2004). However, not all findings have been positive.…”
Section: Recommendation 3: Educate About Gambling Mathematics To Prevmentioning
confidence: 99%
“…In line with these recommendations, studies have started to assess the effectiveness of preventative broad-based adolescent gambling interventions, including those implemented in school settings. One such recent school-based study evaluated the effectiveness of an intervention targeting a general sample of adolescents, including those not deemed to be at risk for problem gambling (Donati et al 2018). The intervention focussed on undermining gambling-related cognitive distortions by reducing probabilistic reasoning errors and superstitious thinking.…”
Section: Community-level Health Promotion Approachesmentioning
confidence: 99%
“…While awareness of problems caused by gambling during adolescence has been steadily increasing, public health responses to this issue have been slow to develop versus other key health concerns in young people. Consequently, research indicates that despite some largely crude government-implemented restrictive and health promotion measures, many minors participate in illegal gambling that places them at a greater risk for problematic gambling behaviour compared to adults (Griffiths 2011;Donati et al 2018). Along with a number of established and emerging psychological theories, research likewise indicates that problem gambling in youth is an expression of underlying problematic behaviours and beliefs.…”
Section: Final Thoughtsmentioning
confidence: 99%